Long‐term endemism of two highly divergent lineages of the amphibian‐killing fungus in the Atlantic Forest of Brazil. Issue 4 (February 2014) - Rodriguez, D.; Becker, C. G.; Pupin, N. C.; Haddad, C. F. B.; Zamudio, K. R.
Abstract The recent global spread of the amphibian‐killing fungus [Batrachochytrium dendrobatidis (Bd)] has been closely tied to anthropogenic activities; however, regional patterns of spread are not completely understood. Using historical samples, we can test whether Bd was a spreading or endemic pathogen in a region within a particular time frame, because those two disease states provide different predictions for the regional demographic dynamics and population genetics of Bd. Testing historical patterns of pathogen prevalence and population genetics under these predictions is key to understanding the evolution and origin of Bd. Focusing on the Atlantic Forest (AF) of Brazil, we used qPCR assays to determine the presence or absence of Bd on 2799 preserved postmetamorphic anurans collected between 1894 and 2010 and used semi‐nested PCRs to determine the frequency of rRNA ITS1 haplotypes from 52 samples. Our earliest date of detection was 1894. A mean prevalence of 23.9% over time and spatiotemporal patterns of Bd clusters indicate that Bd has been enzootic in the Brazilian AF with no evidence of regional spread within the last 116 years. ITS1 haplotypes confirm the long‐term presence of two divergent strains of Bd (BdGPL and Bd‐Brazil) and three spatiotemporally broad genetic demes within BdGPL, indicating that Bd was not introduced into southeast Brazil by the bullfrog trade. Our data show that the evolutionary history and pathogen dynamics of Bd in Brazil is better explained by the endemic pathogen hypothesis.